Biblical Intertexts through the Prism of „the Integrated Approach” [Fundamental Translation Studies Work] - Горнятко-Шумилович, Анна (Poznańskie Studia Slawistyczne, 2018)
The review sets out to provide a critical analysis of Oksana Dzera’s monographic research which has an obvious topicality and interdisciplinary character as the work aims to investigate issues of theory and practice of translation, intertextuality and theolinguistics. The monograph is regarded as a successful project marked with novelty, considerable theoretical and practical value and perspective to open up new vistas for further research.